Effects of targeted temperature management at 33 °C vs. 36 °C on comatose patients after cardiac arrest stratified by the severity of encephalopathy. (April 2022) - Nutma, Sjoukje; Tjepkema-Cloostermans, Marleen C.; Ruijter, Barry J.; Tromp, Selma C.; van den Bergh, Walter M.; Foudraine, Norbert A.; Kornips, Francois H.M.; Drost, Gea; Scholten, Erik; Strang, Aart; Beishuizen, Albertus; van Putten, Michel J.A.M.; et al.
Abstract: Objectives: To assess neurological outcome after targeted temperature management (TTM) at 33 °C vs. 36 °C, stratified by the severity of encephalopathy based on EEG-patterns at 12 and 24 h. Design: Post hoc analysis of prospective cohort study. Setting: Five Dutch Intensive Care units. Patients: 479 adult comatose post-cardiac arrest patients. Interventions: TTM at 33 °C (n = 270) or 36 °C (n = 209) and continuous EEG monitoring. Measurements and main results: Outcome according to the cerebral performance category (CPC) score at 6 months post-cardiac arrest was similar after 33 °C and 36 °C. However, when stratified by the severity of encephalopathy based on EEG-patterns at 12 and 24 h after cardiac arrest, the proportion of good outcome (CPC 1–2) in patients with moderate encephalopathy was significantly larger after TTM at 33 °C (66% vs. 45%; Odds Ratios 2.38, 95% CI = 1.32–4.30; p = 0.004). In contrast, with mild encephalopathy, there was no statistically significant difference in the proportion of patients with good outcome between 33 °C and 36 °C (88% vs. 81%; OR 1.68, 95% CI = 0.65–4.38; p = 0.282). Ordinal regression analysis showed a shift towards higher CPC scores when treated with TTM 33 °C as compared with 36 °C in moderate encephalopathy (cOR 2.39; 95% CI = 1.40–4.08; p = 0.001), but not in mild encephalopathy (cOR 0.81 95% CI = 0.41–1.59; p = 0.537). Adjustment for initial cardiac rhythm and cause of arrest did not change this relationship. Conclusions: Effects of TTM probably depend on the severity of encephalopathy in comatose patients after cardiac arrest. These results support inclusion of predefined subgroup analyses based on EEG measures of the severity of encephalopathy in future clinical trials.